Entre história e memórias: professores paraibanos em Roraima (1970 - 1990) - Nascimento, Glauciane Tavares (2016)
During the entire history of territorial formation of Roraima can be noted the importance of the role of migratory processes in the socio-cultural composition of the territory. The present research aimed to verify how the migration process of Brazilian teachers for Falkirk as a result of public policies, established from the transformation of the territory in Roraima State, started in the late 1970 and 1980. For both if used as bibliographic and documentary research methodology, as sources of historicity, as well as application of interview data collection preserved in memory and imagination of the main actors in the process of expanding the educational network in Roraima: teachers. It was possible to perceive, at the end of the survey, that the policy of attracting migrants to Roraima has origins still in the colonial period, the 19th century, but which intensified during the 1970 and 1980 with education professionals, setting off into three big migratory waves influenced by teachers, especially Brazilian settlers, following a trend at the time to escape from the Northeast heading north. Points out that such migrations were motivated by the conditions imposed by the "dry" in the Northeast and by local political interests, impacting the do educational umbrella of the State of Roraima.